ParC, a New Partitioning Protein, Is Necessary for the Active Form of ParA From Myxococcus pMF1 Plasmid - Sheng, Duohong; Chen, Xiaojing; Li, Yajie; Wang, Jingjing; Zhuo, Li; Li, Yuezhong (Frontiers in Microbiology, 2021)
The ParABS partitioning system, a main driver of DNA segregation in bacteria, employs two proteins, ParA and ParB, for plasmid partition. The pMF1 plasmid from Myxococcus fulvus 124B02 has a par operon encoding a small acidic protein, ParC, in addition to type I ParA and ParB homologs. Here, we show that expression of parC upstream of parA (as in the natural case), but not ex situ, is essential for the plasmid inheritance in Myxococcus cells. Co-expression of parC upstream of parA was determined to form a soluble ParC-ParA heterodimer at a 1:1 ratio, while individual expression of parA or co-expression of parA with ex-situ parC formed insoluble ParA proteins. Purified ParA proteins alone had no ATPase activity and was easily dimerized, while mixing ParA with ParC formed the ParC-ParA heterodimer with the ATPase and polymerization activities. Fusing ParC and ParA also produced soluble proteins and some chimeras restored the ATPase activity and plasmid inheritance. The results highlight that proximal location of parC before parA is critical to realize the functions of ParA in the partition of Myxococcus plasmid pMF1, and shed light on a new mechanism to realize a protein function by two separate proteins.